2016
DOI: 10.3109/11038128.2016.1152295
|View full text |Cite
|
Sign up to set email alerts
|

Feeling like a stranger: negotiations with culture as experienced by Chilean occupational therapists

Abstract: During therapeutic encounters, practitioners and clients may experience cultural barriers even if their differences are not obvious in cultural terms. As a result of this finding, we recommend the inclusion of culture and cultural issues in professional training. The impact of a multicultural research team is discussed. Future research should explore how the construct of culture is introduced in occupational therapy professional training in Chile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…The practitioners realised that mutual cultural learning improved their competencies as OT. Our findings support current concepts of OT in cross-cultural contexts [ 17 , 19 , 72 ]. OT theory and practice built on the diverse cultural background of clients and practitioners can have a relevant and significant impact [ 1 , 20 22 , 81 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The practitioners realised that mutual cultural learning improved their competencies as OT. Our findings support current concepts of OT in cross-cultural contexts [ 17 , 19 , 72 ]. OT theory and practice built on the diverse cultural background of clients and practitioners can have a relevant and significant impact [ 1 , 20 22 , 81 ].…”
Section: Discussionsupporting
confidence: 89%
“…In order to meet the study aims and achieve trustworthiness and credibility, we build a multicultural, multilingual and multidisciplinary research team [ 44 , 65 , 71 , 72 ]. This collaborative approach is increasingly used in cross-cultural research projects [ 72 , 73 ]. The research team included four members.…”
Section: Methodsmentioning
confidence: 99%
“…The contemporary practice stressed on culture competence of the service when dealing with clients (37)(38)(39). Curriculum development that exposed the students to different cultural practice such as conducting fieldwork in different countries and professional training for the practitioners are warranted to produce a cultural competence service (39,40). Our study is consistent with the previous study to promote local cultural practice such as the salat activity to be incorporated in the professional curriculum and training to ensure the service is relevant to Malaysia context.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, recent studies indicated that avoiding including the child in the process of ADHD diagnosis and intervention may have a long-term impact on their understanding of the diagnosis and willingness to continue treatment [50,51] Most of the OTs noted moderate to high transference of therapy goals to the home environment yet also reported a need to address daily routines and habits, as well as cultural values during the intervention process being as these can have an effect both in the routines of the child and the therapist's communication with the parents. The importance of cultural norms and values has been emphasized in previous literature regarding culture and cultural competence [5,9], as well ecological theories, which contend that all activities of the family niche reflect the cultural values and other ecological variables which influence family practices [52]. Therefore, it is important to consider the lifestyle and values of a child's family unit and ethnic group as contextual and environmental factors that may affect their routines and participation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Iwama [4] emphasized the eminent role of culture in OT, making it relevant to diverse clients' occupational needs; as such, it is considered a factor in client collaboration, models of practice, assessment tools, and therapeutic material design. In addition, recent literature addresses the need to understand both the individual client and the collective culture, as well as the interaction between the therapist and the client [5,6].…”
Section: Introductionmentioning
confidence: 99%